Avaliação da virulência e da patogenicidade das cepas MCR, ACFN, ICS, ADO e VEJ de Entamoeba dispar - Cézar Augusto Vilela da Silva (2018)
Entamoeba histolytica produces amebiasis, an infectious disease that affects the human intestine, making it the second largest cause of death among parasitic diseases. Considered commensal, some authors have experimentally reproduced colitis and amebic liver abscess (AHA) using Entamoeba dispar isolated from asymptomatic and symptomatic hosts. Of the strains of E. dispar available in our collection, only MCR was studied in greater detail, analyzing the kinetics of hepatic lesions between 12 hours and 8 days after infection (DAI) and, measuring the lesions. Virulence of the strains of E. dispar from our collection has not yet been evaluated through the erythrophagocitose assay. Many strains have not yet been tested for their pathogenicity and the evolution of AHA after 12 DAI is unknown. The objective of this study was to evaluate the virulence and pathogenicity of E. dispar strains MCR, ACFN, ICS, ADO and VEJ after 3, 8, 12 and 16 days of infection. In the in vitro assay, the trophozoites interacted with human erythrocytes, and the phagocytosed erythrocytes and trophozoites that phagocytosed were counted. Fifteen hamsters were inoculated with 1x105 trophozoites from each strain and, as a control, 1 hamster was inoculated in each group with the native microbiota. Five hamsters from each group were euthanized at 3, 8, 12 and 16 DAI for necropsy, liver collection and processing for histopathology and digital morphometry. All strains of E. dispar were able to phagocyte erythrocytes, with no significant differences between them, but in lesser amounts in relation to E. histolytica. The ACFN strain proved to be pathogenic in the hamster, being able to produce AHA and 100% mortality in periods superior to 8 DAI. On the other hand, MCR produced 29% mortality from the 8th to the 16th DAI, whereas the ICS, VEJ and ADO strains did not cause mortality. AHA was observed in all groups of hamsters, being more frequent in the inoculated with the strains ACFN and MCR. The ACFN produced a necrosis area significantly higher than ADO in the 8th DAI, while necrosis was generated only by the MCR in the 12th DAI. The extent of necrosis was associated with intense parasitism (predominant in the 8th ICD) and usually to the granulocytic, histiocytic or mixed, focal and / or diffuse inflammatory infiltrate (predominantly in the 12th). At the 12th DAI, the last active abscesses were observed and the first ones under repair. Chronic granulomatous inflammation was more frequent in the 8th and 12th DAI, varying between groups. Thrombosis and hemorrhage were more frequent in hamsters inoculated with ACFN, while degenerative phenomena, with the MCR. Most hamsters in the 16th DAI presented preservation of most of the liver parenchyma. Regeneration is the predominant healing mechanism in the experimental amoebiasis produced by E. dispar. Healing occurs in small areas, despite large extensions of granulation tissue. Thus, with the exception of ACFN, all other strains were able to produce self-limiting liver damage.